Analysis of Social work Project Management Process from the Perspective of Empowerment Theory—Taking the "Not Come Singly but in Pairs" Social Work Project for Families Who Lost Their Only Child as an Example - Deng, Yong (Journal of Social Science and Humanities, 2024)
Project-based management of social work has become an important trend in the development of social work, and has gained greater development space for the development of social work. This paper takes the empowerment theory as the theoretical support, takes the "Not Come Singly but in Pairs" social work project for families who have lost their only child as an example, analyzes the project with the four main stages of project management, namely, the initiation, planning, implementation, and closing, and summarizes the experience of social work project management from the perspective of empowerment theory.